Hybrid surgery management challenges of a Behcet's disease patient with recurrence of aortic aneurysms: a case report - Chen, Guo Xin; Wan, Jiang Hong; Chen, Chu Wen; Huang, Bin (Frontiers in Cardiovascular Medicine, 2023)
Background: Behcet's disease is a vasculitis of unknown origin that can involve multiple organs or tissues. Aneurysm or pseudoaneurysm, also one of the complications of Behcet's disease, is usually accompanied by a poor prognosis. Surgery is usually accompanied by a high risk of complications, such as the recurrence of anastomotic pseudoaneurysms and blockage of the target vessel. Using hybrid surgery, we successfully treated a complex and recurrent abdominal aortic pseudoaneurysm in a patient with BD.We report a 32-year-old female diagnosed with Behcet's disease with recurrent thoracoabdominal aortic aneurysm. Adequate immunotherapy was given during the perioperative period. The splanchnic artery branches were reconstructed, and the aneurysm was sequestered with endovascular repair. The patient recovered uneventfully and was discharged from the hospital 8 days after hybrid surgery. At the 60-month follow-up, no aneurysm was observed, the stent had no displacement or internal leakage, and the reconstructed blood vessels were unobstructed.Hybrid surgery could be a feasible and effective strategy for BD aneurysms. Adequate preoperative and postoperative immunotherapy with arterial anastomosis away from the diseased artery may be the key to success.